EFFECT OF TELEREHAB SYSTEM FOR POSTURAL CORRECTION - Yu, JaeHo (International Journal of Psychosocial Rehabilitation, 2020)
As abnormal posture caused by prolonged smartphone use increases, its related disease also increases. It is time to prevent this problem. This study aim to figure out how much telerehab system has an effect on postural correction. Healthy 34 participants were instructed to keep neutral posture and then use smartphone. Each participant was instructed to maintain a neutral posture with their elbows positioned in line with the trunk and flexed 90–120˚ and keep the trunk upright, chin tucked, scapula slightly protracted and depressed and sole of the foot on the floor 1) for 15 minutes in non-feedback condition, after 3 minutes resting period, 2) for 15 minutes in visual feedback condition while maintaining their original posture. When participants consciously apply feedback for postural correction, participants can check the movement of scapula and forward head level as they apply posterior visual feedback. The result of this study had a significant difference in the meaning of interval at Tragus and all Z-coordinate.(p<0.05) Also, there was significant difference in the meaning of cervicoscapular posture angle.(p<0.05) Both results indicated that the participants maintained the original posture well. In this study, it proved that visual feedback for postural correction has a positive effect. Further study needs to demonstrate this measurement to real clinical patients..